Sufficient stability using retrograde cannulated screws in a metacarpal fracture model: a biomechanical evaluation - Heilig, Maximilian; Wagenhäuser, Julian; Huflage, Henner; Heilig, Philipp; Jordan, Martin Cornelius; Jakubietz, Rafael Gregor; Meffert, Rainer Heribert; Hoelscher-Doht, Stefanie (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionThe treatment of metacarpal shaft fractures using cannulated compression screws has become a viable method of osteosynthesis in recent years. However, most biomechanical studies focus primarily on the ultimate failure load, comparing it to plating or K-wires. There is limited biomechanical data how cannulated compression screws perform under realistic cyclic loads encountered during postoperative physiotherapy in comparison to plating.MethodsOblique shaft fractures were created in both porcine metatarsal and human metacarpal bones. Fractures were reduced and treated with either a partially or fully threaded cannulated compression screw or a 2.0 TriLock hand plate. Cyclic loading was then applied for 3,000 cycles, ranging from 10 to 80 N, followed by an ultimate load-to-failure test.ResultsThe displacement after cyclic loading was lower for specimens being treated with a 2.0 TriLock hand plate compared to those treated with an intramedullary compression screw. In the subsequent load-to-failure tests, specimens with a fully threaded intramedullary screw withstood higher forces than those with a partially threaded screw or a plate. Notably, no superiority of the plate was observed in terms of ultimate loading in both porcine and human specimens.DiscussionThe results indicate that using a cannulated compression screw for the treatment of metacarpal oblique fractures provides good biomechanical stability under cyclic loading. Additionally, the use of a fully threaded screw appears to increase the ultimate failure load. This study adds to the biomechanical evidence supporting the use of cannulated compression screws in the treatment of metacarpal oblique fractures. Surgeons should prioritize achieving the best and longest cortical anchorage when selecting the implant to optimize the patient’s outcome.